Virulence and live vaccine potential of EdwardsiellapiscicidaphoP and phoQ mutants in catfish against edwardsiellosis. Issue 9 (26th May 2021) - Sayed, Mohamed; Ozdemir, Ozan; Essa, Manal; Olivier, Alicia; Karsi, Attila; Lawrence, Mark L.; Abdelhamed, Hossam
Abstract: Edwardsiella piscicida is a Gram‐negative facultative intracellular bacterium causing edwardsiellosis in catfish, the largest aquaculture industry in the United States. A safe and effective vaccine is an urgent need to avoid economic losses associated with E. piscicida outbreaks. PhoP/PhoQ is a two‐component signal transduction system (TCS) that plays an important role in bacterial pathogenesis through sense and response to environmental and host stress signals. This study aimed to explore the contribution of PhoQ/PhoP in E. piscicida virulence and develop live attenuated vaccines against E. piscicida infection in channel catfish ( Ictalurus punctatus ) and hybrid catfish (channel catfish ♀ × blue catfish ( I .  furcatus ) ♂). In the current study, two in‐frame deletion mutants were constructed by deleting phoP (ETAC_09785) and phoQ (ETAC_09790) genes in E. piscicida strain C07‐087, and the virulence and protection efficacy of the constructed strains were evaluated in catfish following intraperitoneal injection. Both Ep Δ phoP and Ep Δ phoQ strains had a delayed adaptation to oxidative stress (0.2% H2 O2 ) compared to E. piscicida wild type. The Ep Δ phoP and Ep Δ phoQ mutants produced significantly less biofilm compared to wild‐type E. piscicida . Notably, Ep Δ phoP and Ep Δ phoQ mutants were significantly attenuated in channel catfish compared with wild‐type E. piscicida (6.63% and 4.17% versus 49.16% mortalities), and channel catfish vaccinated with Ep Δ phoP and Ep Δ phoQ were significantly protected (95.65% and 97.92% survival) against E. piscicida infection at 21 days post‐vaccination. In hybrid catfish, Ep Δ phoP was significantly more attenuated than Ep Δ phoQ, but Ep Δ phoQ provided significantly better protection than Ep Δ phoP . Ep Δ phoP and Ep Δ phoQ strains both induced specific antibodies in channel catfish against E. piscicida at 14 and 21 days post‐vaccination. This result indicated that Ep Δ phoP and Ep Δ phoQ mutants were safe and protective in channel catfish fingerlings, while Ep Δ phoP was safe in hybrid catfish. Our findings show that PhoP and PhoQ are required for adaptation to oxidative stress and biofilm formation and may help  E. piscicida face tough environmental challenges; thus, functional PhoP and PhoQ are critical for a successful infection.